Conceptual analysis of the notion of quality of services - Besson , Jérémy; Čaplinskas, Albertas (Lietuvos matematikos rinkinys, 2009)
In the last decade the component technologies have evolved from object-oriented to serviceoriented ones. Services are seen as utilities based on a pay-for-use model. This model requires providing and guaranteeinga certain Quality of Service (QoS). However, QoS and even a service itself can be defined and understood in many different ways. It is by far not obvious which of these approaches and in what extent they should be used when developing service-oriented software systems. This paper analyzes the notion of QoS namely from this point of view.
Keywords: quality of services; component systems; service-oriented approach